2023
DOI: 10.1152/physrev.00023.2022
|View full text |Cite
|
Sign up to set email alerts
|

The multiple roles of salt-inducible kinases in regulating physiology

Abstract: Salt-Inducible kinases, which comprise a family of three homologous serine-threonine kinases were first described for their role in sodium sensing, but have since been shown to regulate multiple aspects of physiology. These kinases are activated or deactivated in response to extracellular signals that are cell surface receptor mediated, and go on to phosphorylate multiple targets including the transcription co-factors CRTC1-3 and the Class IIa histone deacetylases (HDACs). Thus, the SIK family conveys signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 281 publications
0
9
0
Order By: Relevance
“…snap25, tutl). In addition, 3 of the genes peaking at 10:00 (Ap-1, SIK2, Inos) have been reported to function in modulating the core molecular clock in both insects and vertebrates (21)(22)(23). In the group of 31 NS DEGs with peak expression at 10:00, we found 12 genes functioning in neurotransmitter and biogenic amine signaling (e.g.…”
Section: Candidate Genes Involved In Molecular Processes Underlying T...mentioning
confidence: 79%
“…snap25, tutl). In addition, 3 of the genes peaking at 10:00 (Ap-1, SIK2, Inos) have been reported to function in modulating the core molecular clock in both insects and vertebrates (21)(22)(23). In the group of 31 NS DEGs with peak expression at 10:00, we found 12 genes functioning in neurotransmitter and biogenic amine signaling (e.g.…”
Section: Candidate Genes Involved In Molecular Processes Underlying T...mentioning
confidence: 79%
“…At a molecular level, each cell has an intrinsic clock machinery, which is orchestrated by interlinked transcriptional/translational feedback loops [15]. Beyond the regulation through this core circadian machinery, other protein families have been identified that contribute to circadian regulation, among others salt inducible kinases (SIKs) which consist of three members: SIK1, SIK2, and SIK3 [16]. SIKs convey signals through phosphorylation of multiple targets, the best understood of which are class IIa histone deacetylases (HDACs) and cAMP-regulated transcriptional coactivators (CRTCs) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SIK expression, activity, and cellular localization can change in response to numerous physiological signals. It is therefore not surprising that the SIK kinases have been shown to regulate a multitude of physiological functions as recently reviewed by Jagannath and Darling ( 1 , 2 ). Apart from being identified as key metabolic regulators, the SIK proteins have been shown to control bone formation and inflammation by modulating macrophage and mast cell function.…”
mentioning
confidence: 99%
“…Although the three SIK isoforms share similar structures and targets, they play both distinct and redundant roles in regulating physiological processes. Since the initial discovery of SIK1 and its involvement in the cell’s ability to adapt to variation in cellular sodium concentration ( 7 , 8 ), a very complex picture of the role of individual SIK isoforms or combinations thereof has emerged as thoroughly described in recent reviews ( 1 , 2 , 9 , 10 , 11 ).
Figure 1 Domain organization of the 3 SIKs.
…”
mentioning
confidence: 99%
See 1 more Smart Citation